Diritto e violenza Un'analisi giusletteraria - FERSINI, MARIA PINA (Premio Ricerca «Città di Firenze», 2018)
With the rise of modernity, law faces an irreducible contradiction. It must stem the State's available strength, while at the same time use this strength to make its decisions binding. The author, starting from this paradox, analyses the legal, philosophical and literary discourses of modernity to find the right tools to properly differentiate law and "vis", overcoming two philosophical and juridical traditions: the one depicting law as a Leviathan, and the one wanting to make it immune to all forms of violence. In particular, through an unedited reading of Kafka and Melville's narratives, she demonstrates how the modern legal systems, rather than just being instruments of control, are dreams and fantasies of non-violence.